2020
DOI: 10.3390/brainsci10060342
|View full text |Cite
|
Sign up to set email alerts
|

New Directions in Exercise Prescription: Is There a Role for Brain-Derived Parameters Obtained by Functional Near-Infrared Spectroscopy?

Abstract: In the literature, it is well established that regular physical exercise is a powerful strategy to promote brain health and to improve cognitive performance. However, exact knowledge about which exercise prescription would be optimal in the setting of exercise–cognition science is lacking. While there is a strong theoretical rationale for using indicators of internal load (e.g., heart rate) in exercise prescription, the most suitable parameters have yet to be determined. In this perspective article, we discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 291 publications
(454 reference statements)
0
35
0
Order By: Relevance
“…fNIRS is an optical neuroimaging technique enabling significant advances in the understanding of functional brain activity and higher cognitive functions [ 32 , 33 ]. This non-invasive technique is based on optical spectroscopy and detecting correlates of brain activity mediated by neurovascular coupling (NVC) [ 34 ]. A typical NVC response, due to increased neuronal activity, consists of an increase in oxygenated ([O 2 Hb]) and total ([tHb]) hemoglobin and a simultaneous decrease in deoxygenated hemoglobin ([HHb]) [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…fNIRS is an optical neuroimaging technique enabling significant advances in the understanding of functional brain activity and higher cognitive functions [ 32 , 33 ]. This non-invasive technique is based on optical spectroscopy and detecting correlates of brain activity mediated by neurovascular coupling (NVC) [ 34 ]. A typical NVC response, due to increased neuronal activity, consists of an increase in oxygenated ([O 2 Hb]) and total ([tHb]) hemoglobin and a simultaneous decrease in deoxygenated hemoglobin ([HHb]) [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Valid indicators that represent the most appropriate proxies of dose for prescribing physical interventions are highly specific and more research is needed to identify them (with regard to the context and/or specific acute or chronic responses) [ 18 ]. In this regard, current concepts discuss promising internal load parameters (e.g., brain-derived parameters, hormones) to prescribe physical exercise, in addition to traditional measures like heart rate, blood lactate concentration, or rating of perceived exertion [ 36 ]. Nevertheless, there is a good, at least theoretical, rationale in support of the individualization of exercise and training prescription by providing a distinct (comparable and standardizable) dose across individuals to elicit the desired psychophysiological responses, which would in turn allow for a better comparison of outcomes across different individuals [ 2 , 37 , 38 ].…”
Section: Implications and Areas For Future Researchmentioning
confidence: 99%
“…Wang et al [ 9 ] in a cross-over double-blind study showed that ingestion of a low dose of caffeine had greater positive effects on intermittent exercise (mimicking team sports) and cognitive performance (perceptual-motor speed, executive information processing) than a moderate or high dose of caffeine. In a double-controlled experimental design study, Brietzke et al [ 10 ] showed that a carbohydrate mouth rinse might counteract mental fatigue effects on exercise performance, despite comparable cortical activation assessed by functional near-infrared spectroscopy (fNIRS), an optical neuroimaging method that allows for measuring brain tissue concentration changes in oxygenated and deoxygenated hemoglobin in the cortical layers during exercise [ 11 ]. The benefit of applying functional neuroimaging methods, such as fNIRS or EEG, in the field of exercise-cognition research, allows the investigation of to what extent exercise-induced changes in neural processes underlie behavioral outcomes; these methods are presenting a growing interest [ 10 , 11 , 12 , 13 ].…”
mentioning
confidence: 99%
“…In a double-controlled experimental design study, Brietzke et al [ 10 ] showed that a carbohydrate mouth rinse might counteract mental fatigue effects on exercise performance, despite comparable cortical activation assessed by functional near-infrared spectroscopy (fNIRS), an optical neuroimaging method that allows for measuring brain tissue concentration changes in oxygenated and deoxygenated hemoglobin in the cortical layers during exercise [ 11 ]. The benefit of applying functional neuroimaging methods, such as fNIRS or EEG, in the field of exercise-cognition research, allows the investigation of to what extent exercise-induced changes in neural processes underlie behavioral outcomes; these methods are presenting a growing interest [ 10 , 11 , 12 , 13 ]. The study of Brietzke et al [ 10 ] provided an example of a rigorous, well-controlled methodology to assess EEG responses over the prefrontal cortex and primary motor cortex areas at different controlled intensities below 75% of the maximal power output during a maximal incremental cycling test.…”
mentioning
confidence: 99%
See 1 more Smart Citation